Enhancement of growth performance and hematological changes in rainbow trout (Onchorhynchus mykiss) alevins fed with Bifidobacterium bacteria - Javad Sahandi; Hojatollah Jafaryan; Mehdi Soltani; Pouneh Ebrahimi (Journal of Fisheries, 2017)
The study of probiotic application as an important rearing strategy was started more than 30 years ago and most of these studies were carried out to increase growth and survival of larvae. Effect of Bifidobacterium animalis PTTC-1631 and B. lactis PTTC-1736 as probiotic supplement has been studied on growth performance and hematological changes on rainbow trout, Oncorhynchus mykiss alevins with initial body weight of 0.583 ± 0.197 g. The commercial diet was supplemented with graded levels of probiotics (1×107, 2×107 and 3×107 CFU g-1 dry feed) to obtain 3 sets of experimental diets (T1, T2, and T3 respectively) and fed four times a day for 60 days. T1 alevin showed the best growth performance in terms of specific growth rate, weight gain, metabolic growth rate, feed conversion ratio and survival rate. The highest red and white blood cell concentrations were noticed in fish fed T2 and T3 diets, respectively, no significant difference was observed in hemoglobin content. T1 showed the significant elevation of serum biochemical parameters and reduction of cortisol level. The results of present study might suggest likely positive effects of probiotic supplements with concentration of 1×107 CFU g-1 dry feed on growth and hematology on rainbow trout alevins.